Prototipo de sistema electrónico para la adquisición de datos que permitan caracterizar el recurso solar aprovechable de una zona determinada - Torres-Moreno, Josué (Instituto Tecnológico de Costa Rica, 2017)
In this project is introduced a design, implementation, and evaluation of a prototype created to obtain data that could be used to obtain approximately the amount of usable solar resource. For this application it's used libraries like OpenCV and K-means Clustering for image analysis of sky, also variables such as global irradiance, temperature, humidity, etc, to characterize the environment. This prototype established a rst stage to ITRC to obtain a percentage values about usable solar resource to be corroborated with theoretical data in di erent zones.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2017.
Keywords: Cámara; DSP; Espectro; K-means; Panel fotovoltaico; OpenCV; Potencia